Optimal timing of surgery in head and neck squamous cell carcinoma after neoadjuvant immunochemotherapy - Seng, Hanbo; Fan, Yunli; Zhao, Rui; Liu, Yanyan; Meng, Jinping; Wang, Ziqi; Chen, Yanyan; Shao, Shengli; Seng, Dongjie (Frontiers in Oncology, 2026)
ObjectivesOur goal was to evaluate the influence of the interlude between neoadjuvant immunochemotherapy (NAIC) and surgery on both pathologic responses and surgical outcomes in head and neck squamous cell carcinoma (HNSCC).MethodsPatients undergoing surgery for HNSCC following NAIC were retrospectively enrolled and determined based on the time to surgery (TTS). Impact of TTS on major pathologic response (mPR), pathologic complete response (pCR), surgical complication and 3-year disease free survival (DFS) was evaluated.ResultsA total of 356 patients were enrolled. 225 patients (63.2%) achieved a mPR, among whom a pCR was achieved in 104 patients (29.2%). When compared to the TTS<1 week group, patients with a TTS of 1-2 weeks and those with a TTS of 2-3 weeks exhibited comparable rates of pCR and mPR achievement; however, patients who underwent surgery more than 3 weeks after the completion of NAIC had a significantly reduced likelihood of achieving total tumor regression by 16% (95% CI: 1%-23%) and lower probability of major tumor regression by 21% (95% CI: 5%-36%). The TTS >3 weeks group bore an additional 0.67-fold risk of experiencing surgical complications and 1.23-fold increased risk of adverse recurrence or death events compared to TTS <1 cohort.ConclusionA TTS exceeding 3 weeks was independently associated with a diminished likelihood of achieving both pCR and mPR, an increased rate of surgical complications, and a shorter duration of DFS. These findings suggest that the interval between surgery and the completion of NAIC may be optimal when kept within 3 weeks in HNSCC, though this warrants prospective validation.